Challenges of respondent driven sampling to assess sexual behaviour and estimate the prevalence of human immunodefi ciency virus (HIV) and syphilis in men who have sex with men (MSM) in Singapore - Chua, A.C. (2014)
Annals of the Academy of Medicine Singapore